The Influence of Love of Money, Financial Self-Efficacy, and Digital Business Literacy on the Financial Performance of MSMEs Using Digital Finance (A Case Study of Fashion Thrift in Mataram City) - Nabila Okta Sumita; Adhitya Bayu Suryantara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Love of Money, Financial Self-Efficacy, and Digital Business Literacy on the Financial Performance of MSMEs, specifically in thrift businesses in Mataram City. The sampling technique used is purposive sampling, with thrift business owners in Mataram City selected as the sample. Data was collected through a questionnaire distributed via Google Forms and analyzed using SmartPLS software. The analysis results show that Love of Money and Digital Business Literacy have a positive but not significant influence on the Financial Performance of MSMEs, while Financial Self-Efficacy has a significant positive influence on the Financial Performance of MSMEs. This research provides valuable insights into the factors that need to be considered by MSMEs, particularly thrift entrepreneurs, to achieve better and more sustainable financial performance.